OLYMPIC FIGHT IN WOMEN: ADHERENCE AND RETENTION (Fiep Bulletin - online, 2012)
The present study is to show the process of legalization of women's fight as a competitive sportin Brazil, increasingvisibility in wrestling, particularly feminine style, and encourage adherence to the feminine sport. Given these perspectives, thisstudy proposes to understand how women of the Brazilian wrestling inserted themselves in this sport and are motivated to staythere. The research presented here is characterized by qualitative and descriptive. In addition a detailed literature about femaleparticipation in sports and fights. The wrestling women's style of high performancefeatures only 4 (four) categories of weight forthis reason we chose to interview the four athletes of the Brazilian Olympic Fight, which are considered the elite informants. Thesurvey instrument used wasadapted from the master's thesis developed by the University Gama Filho Souza and Mourao (2008)which tells the history of judo fighters for the Brazilian team from 1979 to 1992, trying to understand what were the reasons formembership, retention and the difficulties faced by them in judo.They also compared the situations of admirers andpractitionersof other sports men said. Despite the difficulties encountered in the daily struggle ofwomen, the changes in the body and thenumber ofmen in training, there was no record of prejudice.Very different to the situation described by the references cited herein.
Keywords: Olympic Fight; Fight; Fight Women